The Voices for Healthy Kids Campaign and US State Legislation to Prevent Childhood Obesity - Bleich, Sara N. (Am J Public Health, 2016)
We documented childhood obesity legislative activity in all 50 US states that occurred in parallel to the first year of Voices for Healthy Kids (Voices), a campaign to mobilize evidence-based legislation addressing childhood obesity. We identified 217 bills in the year before Voices (November 2012 to October 2013) and 304 bills at follow-up (November 2013 to October 2014). In states with active Voices grantees, the bill enactment rate was 50% higher (increasing from 10% at baseline to 15% at follow-up).